Common carotid artery endovascular clamping for neuroprotection during carotid stenting: Flow‐gate system as an innovative treatment approach. Issue 1 (28th September 2020) - Gabrielli, Roberto; Castrucci, Tommaso; Siani, Andrea; Accrocca, Federico; Rizzo, Anna Rita; Spinelli, Alessio; Cancellieri, Roberto; Bartoli, Stefano
Abstract: Objectives: We here report our clinical experience in CAS management through common carotid artery endovascular clamping with FlowGate2 system. Methods: Forty‐five patients were enrolled with de novo asymptomatic internal carotid artery stenosis ≥70%. Cerebral protection during the stenting procedure was achieved using a unique endovascular clamping technique developed in our Institution which includes: (a) the occlusion of the common carotid artery only, through inflatable balloons integrated in the FlowGate2 Balloon Guide Catheter system; (b) flow inversion connecting catheter to 16 G blood cannula previously placed in arm vein; (c) after the placement of the stent, the flow inversion is maintained for 30 s to allow debris washout. The related primary end‐point was the rate of Diffusion‐weighted imaging magnetic resonance (DWI) micro‐embolic scattering of infarction. The patient's clinical and the neurological status were assessed prior, during and after intervention, at discharge. Results: Transient clamping intolerance was observed in two patients (2/45; 4%). One minor stroke (1/45; 2%) occurred 8 hr the procedure with DWI ipsilateral micro‐embolic lesions. No major strokes or deaths were observed at 3 months follow‐up. DWI demonstrated ipsilateral micro‐embolic scattering of infarction, in one asymptomatic patient. In all patients, no worst changes in NIHSS scale assessment were recorded at 1, 3, and 6 months. Conclusions: Our data confirmed the efficacy of FlowGate2 in terms of neuroprotection during CAS. To our knowledge, these are the first published data on this innovative approach developed in our institution. A large controlled trial is ongoing to confirm preliminary evidences.